Effects of hormonal treatments on spawning latency and egg production of captive silver trevally (Pseudocaranx georgianus) - Matthew J. Wylie; Flavio F. Ribeiro; Warren Fantham; Morgan E. Puklowski; Ria Rebstock; Nicola Shaw; Constantinos C. Mylonas; Keitaro Kato; Abigail Elizur; Maren Wellenreuther (Aquaculture Reports)
Controlling reproduction is a vital step in aquaculture to ensure the production of high-quality fertilized eggs in adequate quantities. The silver trevally (Pseudocaranx georgianus) is a candidate for the diversification and expansion of the New Zealand aquaculture sector, but initial research showed that it fails to spawn spontaneously in captivity. Therefore, we induced spawning in wild-caught, captivity-acclimated broodstock using an agonist of gonadotropin-releasing hormone (GnRHa) in slow-release implants or an injection of human chorionic gonadotropin (hCG). The GnRHa implants at a dose of 83–152 μg kg−1 body weight (BW) for females and 58–167 μg kg−1 BW for males induced spawning with latency times of 2 days post-administration. The hCG injection at a dose of 600 IU kg−1 BW for both males and females induced spawning with latency times of 8 days post-administration. Total egg production was comparable between GnRHa (∼ 2.8 million eggs kg−1 BW) and hCG treatments (∼ 3.5 million eggs kg−1 BW) with egg quality being variable and having a high percentage non-fertilized and dead eggs (66–84 %). On average, egg diameter and total body length of newly-hatched larvae were significantly larger from GnRHa-treated fish compared to those from hCG-treated fish (P = 0.0121 and P < 0.0001, respectively), while the average oil globule diameter of newly-hatched larvae was significantly smaller from GnRHa-treated fish compared to those from hCG-treated fish (P = 0.0062). Both hormonal treatments demonstrated “proof-of concept” in silver trevally by spawning adequate numbers of eggs, but optimization of the treatment is necessary (dose, administration time, etc.), to achieve better egg viability and fertilization success.